B305 Improving discharge prescribing: developing a multi-centre educational intervention. (11th August 2022) - Nolan, R; O'Gara, A; Marsh, H; Roche, D; O'Gorman, L; Shinnors, S; Leddy, L; Hearty, C
Abstract : Background and Aims: (Ethics Approval) Thousands of surgeries are performed in Ireland every year, with patients being cared for by expert multidisciplinary teams, including consultant surgeons and anaesthetists. Prescriptions for analgesia upon discharge, however, are often left to the most junior of the surgical team, with little oversight. We undertook a multi-site service evaluation and quality improvement project which interrogated current analgesic prescribing patterns. We then instituted a number of educational tools to assist junior doctors in good-practice prescribing upon discharge. Methods: Retrospective chart review of surgical patients from two tertiary hospitals in Dublin, Ireland, from December 2020 to March 2021 &amp August 2021 to September 2022. Opioid tolerant and chronic pain patients were excluded. We created a flowchart algorithm ( Figure 1 ) adapted from guidelines [1] and educated junior doctors on its use through lectures. Results: 200 patients were included. There was initially large interdiscipline variability in the average milligram morphine equivalents (MMEs) prescribed, as well as interpatient variability and dangerous co-prescription of opioids. Our guidance had excellent uptake from junior doctors and the average MME on discharge fell from 181mg to 90mg (site 1) & 148mg to 94mg (site 2). Overall appropriate opioid prescription rose in both sites from 64% to 75% (site 1) & 57% to 92% (site 2). Appropriate prescription of simple analgesia was increased by 23%. Conclusions: Our flowchart algorithm and educational sessions are effective, cost-neutral methods to reduce overprescription of opioids and increase good-practice prescribing on discharge, which is of huge benefit to the wider community.